Elaboración del estudio de prefactibilidad para el montaje de una empresa para ofrecer servicios de taxi seguro por medio de dispositivos móviles en la ciudad de Bogotá (2014)
The project consists of the development of an application for mobile devices for safe taxi service in the city of Bogotá, which allows verification of taxi registration prior to boarding, thus reducing the risk of being a victim of the crime of express hijacking, known as "millionaire ride". This application will also have other features that provide convenience, such as the request for services door to door, assigning only previously verified taxis. This document includes the pre-feasibility study to evaluate the feasibility of creating a company to offer taxi services through mobile devices in the city of Bogotá. For its realization, the stages of Identification and Strategic Alignment of the Project were developed with the Development Plan 2012 - 2016, Bogotá Humana of the Mayor's Office of Bogotá; Formulation including market, technical, administrative, cost and benefit, financial and financing studies, financial evaluation and, finally, the project management plan.